Using Cognitive Interviews to Adapt Interpersonal Violence Measures for Use With Middle School Youth - Adhia, Avanti (Journal of interpersonal violence, 2024)
Experiences of interpersonal violence are common among youth. Starting prevention programming early (e.g., middle school) may be beneficial for primary prevention. Evaluating whether such programs are effective often requires collecting self-report data from youth, but many existing measures have been developed for high school and college-aged youth. This study aimed to assess adolescents’ comprehension of self-report survey items on interpersonal violence with middle school youth. We conducted virtual cognitive interviews with 15 youth in grades 6 to 8. A content analysis was used to identify patterns and to classify the nature and type of comprehension issues youth experienced. Nearly all students found most questions clear and understandable. We identified the following comprehension issues: (1) uncertainty with how the intent of a perpetrator factored into a victim’s experience (e.g., distinguishing the difference between joking and bullying, or intentional versus unintentional behavior); (2) lack of familiarity with certain expressions of sexualized violence (e.g., “sexual looks”) or sex-related terminology (e.g., intercourse); and (3) narrow interpretations of question prompts (e.g., interpreting “forced” as physically forced, not psychologically coerced). Students suggested including language describing dating relationships, types of social media platforms where cyber abuse takes place, and additional examples alongside items to enhance relevance and clarity. Survey questions to measure interpersonal violence may need to be adapted for use among middle school youth. Our findings highlight potential considerations for improving the measurement of interpersonal violence in this age group.